1999
DOI: 10.1046/j.1365-2982.1999.00132.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive evoked potentials to anticipated oesophageal stimulus in humans: quantitative assessment of the cognitive aspects of visceral perception

Abstract: Evoked potential studies provide an objective measure of the neural pathways involved with perception. The effects of cognitive factors, such as anticipation or awareness, on evoked potentials are not known. The aim was to compare the evoked potential response to oesophageal stimulation with the cortical activity associated with anticipation of the same stimulus. In 12 healthy men (23.5 +/- 4 years), oesophageal electrical stimulation (15 mA, 0.2 Hz, 0.2 msec) was applied, and the evoked potentials recorded us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The application of CEP methodologies to study gastrointestinal afferent sensory function provides an objective and quantifiable approach to examine the contribution of different sensory pathways in health, as well as under pathological conditions 27 . 29 , 33 , 40 –50 However, only one previous study investigated the yield of CEP responses in patients with NCCP 51 . Smout et al .…”
Section: Discussionmentioning
confidence: 99%
“…The application of CEP methodologies to study gastrointestinal afferent sensory function provides an objective and quantifiable approach to examine the contribution of different sensory pathways in health, as well as under pathological conditions 27 . 29 , 33 , 40 –50 However, only one previous study investigated the yield of CEP responses in patients with NCCP 51 . Smout et al .…”
Section: Discussionmentioning
confidence: 99%
“…Findings in imaging studies may be biased as they reflect a combination of early pain-specific and later nonpain-specific neural activity [27,28]. On the other hand, Hollerbach et al [34] have shown that evoked potentials to anticipated oesophageal stimuli produce endogenous but not exogenous responses, whereas responses to actual oesophageal stimuli contain both. Being able to differentiate between endogenous and exogenous activity is an advantage as new analgesics in drug development aim at modulating the exogenous pain-specific responses [35].…”
Section: Advantages Of the Current Methodmentioning
confidence: 99%
“…[1][2][3][4] In IBS, for example, a number of findings favour a psychological rather than a biological basis for increased pain sensitivity. First, IBS patients often rate even sham distensions as painful.…”
mentioning
confidence: 99%